Treatment of wastewater sludge by liquid state bioconversion process - Alam, Md. Zahangir; Fakhru'l-Razi, A.; Molla, Abul Hossain; Roychoudhury, P. K. (Informa UK Limited, 2001)
This study was conducted to evaluate the effect of an eminent decay fungus, Phanerocheate chrysosporium of organic residues on wastewater sludge for its improvement through decomposition and separation of waste particles by Liquid State Bioconversion (LSB). The effect of fungal treatment was compared to uninoculated (Control) at three different harvests 7, 14 and 21 days after inoculation (DAI). The observed results showed that the weight loss and solid content of wastewater sludge were significantly influenced by Phanerocheate chrysosporium. Both parameters were highly influenced at 7 DAI. The COD and pH of wastewater sludge were also highly influenced by fungal treatment.